2021
DOI: 10.1007/s11259-021-09867-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bacterial organic selenium, selenium yeast and sodium selenite on antioxidant enzymes activity, serum biochemical parameters, and selenium concentration in Lohman brown-classic hens

Abstract: This study compares the effects of sodium selenite, selenium yeast, and enriched bacterial organic selenium protein on antioxidant enzyme activity, serum biochemical pro les, and egg yolk, serum, and tissue selenium concentration in laying hens. In a 112-d experiment, 144 Lohman Brown Classic hens, 23wks old were divided into four equal groups, each has six replicates. They were assigned to 4 treatments: 1) a basal diet (Con), 2) Con plus 0.3 mg/kg feed sodium selenite (SS); 3) Con plus 0.3 mg/kg feed Seyeast … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 114 publications
1
4
0
Order By: Relevance
“…In this work, dietary 0.01 and 0.05 g/kg DCH supplementation increased the contents of CAT and SOD in the serum of laying hens relative to the control group, indicating that DCH played an antioxidant effect by increasing the levels of antioxidant enzymes. This is consistent with previous reports that the addition of bacterial organic selenium or Se-yeast in the diet increased glutathione peroxidase (GSH-Px), CAT, and SOD activity in laying hens ( 38 ). Sun et al used selenium-enriched earthworm powder as an additive to feed laying hens, observing the improvement of antioxidant activity and immune response ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this work, dietary 0.01 and 0.05 g/kg DCH supplementation increased the contents of CAT and SOD in the serum of laying hens relative to the control group, indicating that DCH played an antioxidant effect by increasing the levels of antioxidant enzymes. This is consistent with previous reports that the addition of bacterial organic selenium or Se-yeast in the diet increased glutathione peroxidase (GSH-Px), CAT, and SOD activity in laying hens ( 38 ). Sun et al used selenium-enriched earthworm powder as an additive to feed laying hens, observing the improvement of antioxidant activity and immune response ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al [18] reported the antioxidant effect of selenium supplementation. Muhammad et al [19] studied the effects of different sources of Se on hepatic total antioxidant capacity, GSH-Px, and CAT activity, which are all increased by selenium administration. The addition of selenium in animal feeds increases the animal's immune state and the ability of the immune system to respond to experimental challenges [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study the effect of selenium in blood serum the catalase level show higher (P≤0.05) in group E in comparison to positive control. A similar experiment was conducted by Muhammad et al (2022) who reported that the Se is an integral part of different antioxidants enzymes. The antioxidants capability of Se, which reduce the proceed of lipid peroxidation and scavenging the free radicles.…”
Section: Effect Of Selenium On Redox Status In the Blood Serummentioning
confidence: 71%